2014
DOI: 10.1073/pnas.1321364111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of the evolution of carbapenem-resistant multilocus sequence type 258 Klebsiella pneumoniae

Abstract: Infections caused by drug-resistant bacteria are a major problem worldwide. Carbapenem-resistant Klebsiella pneumoniae, most notably isolates classified as multilocus sequence type (ST) 258, have emerged as an important cause of hospital deaths. ST258 isolates are predominantly multidrug resistant, and therefore infections caused by them are difficult to treat. It is not known why the ST258 lineage is the most prevalent cause of multidrug-resistant K. pneumoniae infections in the United States and other countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
365
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(391 citation statements)
references
References 21 publications
22
365
2
2
Order By: Relevance
“…Indeed, ST258 strains were distinct by genotypes (presence of particular molecular mechanisms of antimicrobial resistance) and/or phenotypes (antimicrobial susceptibility profiles). Our data add to a growing body of evidence that ST258 K. pneumoniae strains are highly heterogenous, despite being considered clonal by conventional molecular epidemiologic criteria (5,(26)(27)(28)(29)(30). We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Indeed, ST258 strains were distinct by genotypes (presence of particular molecular mechanisms of antimicrobial resistance) and/or phenotypes (antimicrobial susceptibility profiles). Our data add to a growing body of evidence that ST258 K. pneumoniae strains are highly heterogenous, despite being considered clonal by conventional molecular epidemiologic criteria (5,(26)(27)(28)(29)(30). We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29).…”
Section: Discussionmentioning
confidence: 51%
“…We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29). Recent studies from our group and others have demonstrated striking diversity in the core genome of ST258 K. pneumoniae strains, including strains recovered from patients at single centers or longitudinally from the bloodstreams of individual patients (26,28). Variations in plasmid content and number are associated with differences in multidrug resistance patterns (26).…”
Section: Discussionmentioning
confidence: 86%
“…Several recent genomic analyses indicate that sequence type (ST) 258 is a recombinant strain that has undergone capsular exchange since its emergence as a cause of KPC outbreaks (28)(29)(30). However, little attention has been paid to other MDR clones, which also are common and can spread carbapenem resistance (31).…”
Section: Significancementioning
confidence: 99%
“…Because of the genetic variations in the bacterial strains and the difference in the frequency of antibiotic use, a drug resistance rate varies widely in different regions of the world. Hence, identifying important and common hospital pathogens and determining the exact pattern of antibiotic resistance could be of use for the control of outbreaks and reduction of treatment costs (18,19). The resistance rates reported in studies from different provinces of Iran have been inconsistent.…”
Section: Conflict Of Interestmentioning
confidence: 99%